The coordinating function of the prosecution authorities of Kazakhstan to combat crime (Journal of actual problems of jurisprudence, 2018)
This article explores the coordinating role of the prosecution in the Republic of Kazakhstan. By securing a fight against crime prosecution authorities act not only as a supervisory authority, but as a coordinator. We consider the position of the Coordinating Council of the Republic of Kazakhstan, reviewed the provisions of the legislation of the Republic of Kazakhstan. Key words: Law enforcement agencies, prosecutor’s office, coordinating functions, crime, mutual exchange, investigation and inquiry.